2011
DOI: 10.1002/dvdy.22547
|View full text |Cite
|
Sign up to set email alerts
|

Role of chromatin remodeling gene Cecr2 in neurulation and inner ear development

Abstract: The loss of Cecr2, which encodes a chromatin remodeling protein, has been associated with the neural tube defect (NTD) exencephaly and open eyelids in mice. Here, we show that two independent mutations of Cecr2 are also associated with specific inner ear defects. Homozygous mutant 18.5 days post coitus (dpc) fetuses exhibited smaller cochleae as well as rotational defects of sensory cells and extra cell rows in the inner ear reminiscent of planar cell polarity (PCP) mutants. Cecr2 was expressed in the neuroepi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…CECR2 contributes to sperm fertility and may regulate Dlx5 in the testis CECR2 plays important roles in neurulation and inner ear development, 10,19 but its functional roles in adult tissues have not been explored. In the present study, we found that CECR2 influences the ability of spermatozoa to fertilize oocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CECR2 contributes to sperm fertility and may regulate Dlx5 in the testis CECR2 plays important roles in neurulation and inner ear development, 10,19 but its functional roles in adult tissues have not been explored. In the present study, we found that CECR2 influences the ability of spermatozoa to fertilize oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The Cecr2 Gt45Bic gene trap mutation on BALB/c background (Cecr2 Gt ) was generated previously and genotyped by multiplex PCR. 10,19 For our initial fertility testing (see Fig. 1), 11 BALB/c Cecr2 Gt45Bic mutant males and 23 wild-type males between ages of 10 and 24 weeks were each set up in mating pairs to wild-type females and left together for 3 months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 SLC25A18 catalyzes unidirectional transport of glutamate in the inner membranes of mitochondria. 19 ATP6V1E1 codes for the regulatory accessory subunit E of the vacuolar-type H(+)-ATPase, which is responsible for acidification of intracellular organelles and involved in hydrogen ion transport across the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report has shown that the ATPdependent chromatin-remodeling enzyme CHD7 regulates proneural gene expression and neurogenesis in the inner ear but might function in parallel with Eya1 (Hurd et al, 2010). Another ATP-dependent chromatin-remodeling protein CECR2 has also been reported to be involved in inner ear development (Dawe et al, 2011). It will be interesting to test whether there is functional redundancy or crosstalk between these different ATP-dependent chromatin-remodeling complexes in mediating neuronal differentiation in the inner ear.…”
Section: Requirement Of the Swi/snf Complex For Mediating The Transcrmentioning
confidence: 99%